From schools to the streets: from an occupation of the self to an urban aesthetic-politics - Pimentel, Mariana; Vasconcellos, Jorge (Farol, 2024)
We propose to think of secondary school occupations as devices of artistic subjectivation, since they established another way of inhabiting the school space and carrying out urban actions. We argue that students reinvented themselves by activating an aesthetic of the self while simultaneously carrying out urban actions through aesthetic-political and performative procedures, activating ways of operating that are specific to the field of art, mixing up the division of the sensitive between what is art and what is activism.